Malenʹkai͡a print͡sessa - Burnett, Frances Hodgson, 1849-1924 (Li͡ubimoe chtenie., 2006)
Sara Crewe, a pupil at Miss Minchin's London school, is left in poverty when her father dies but is later rescued by a mysterious benefactor.